Strategi Pengelolaan Hutan Kemasyarakatan dalam Perspektif Ekonomi, Ekologi, dan Sosial: Studi Kasus Kelompok Tani Sedyo Makmur di Gunung Kidul, D.I. Yogyakarta - Pradito Mushandono; Soni Trison; Leti Sundawati (Postgraduate, University of Mataram, 2025)
Community forests play a crucial role in improving rural livelihoods, yet their management often faces challenges related to low income contribution, ecological sustainability, and limited social empowerment. This study aims to analyze the economic, ecological, and social benefits of community forest management and to assess their contribution to the welfare of members of the Sedyo Makmur Farmer Group in Gunung Kidul, Special Region of Yogyakarta. The research employs a descriptive case study approach by combining qualitative and quantitative methods, including interviews, direct observations, and analysis of household income. Data were examined using income contribution analysis and SWOT analysis to identify strengths, weaknesses, opportunities, and threats in forest management. The results show that community forest management provides benefits in three dimensions. Economically, community forests contribute 29.32% to household income, complemented by secondary crops and livestock. Ecologically, applying variable planting spacing improves tree growth and ecosystem conservation. Socially, forest management fosters collective action and diversifies livelihood strategies. The study concludes that optimal management strategies should focus on product diversification, member capacity building, and ecotourism development. These strategies are expected to enhance welfare, ensure sustainability, and strengthen the role of community forests within social forestry programs.